Influencia del Manejo del Archivo en la Gestión Secretarial del Centro de Perfeccionamiento Docente e Innovación Pedagógica de la Universidad Nacional de Chimborazo, período Julio – Diciembre 2014. - Redrobán Dillón, Josett Carolina (2016)
This research was conducted at the Center for Teacher Training and Educational Innovation at the Universidad Nacional de Chimborazo, its performance was important to have knowledge of the functions performed by the secretary of this unit, the organization, the attitude, the attention, the customer service, but mainly identify their work activities undertaken to improve the institution, during this investigation it has been found that these activities were well executed by the person in charge, but there was also the need to elaborate a file management manual in which the functions, processes and activities are well detailed so that the Secretarial work is better organized therefore help preserve the past and current documents properly, if it is executed it will also help other secretaries at Universidad Nacional de Chimborazo. This Manual contains the processes and parameters that the preservation of files and everything else the Higher Institution must have so this research work has been divided into chapters which explains in detail how is structured the thesis, as follows: in the first chapter it has included the problem, formulation, objectives and justification of research work, in the second chapter the main theoretical basis of the subject in question, the operationalization of the variables was performed in both the Independent Variable and Dependent Variable, in the third chapter the research methodology as scientific analysis and synthesis methods were applied, as techniques the survey to teachers and direct observation to the secretary were applied at place work the questionnaire and observation sheet were used as tools. Conclusions and recommendations were made at the end, bibliography, annexes and then the last chapter as an alternative proposal a management and file organization manual was done as contribution for Teacher Training and Educational Innovation Center at the Universidad Nacional de Chimborazo.